Effects of Positive Corona Discharge on PH Value of Tap and Distilled Waters in Liquid system - Abbas, Qusay Adnan (Al-Nahrain Journal of Science, 2013)
In this paper, the effect of positive corona discharge on the PH values of tap and distilled waters are studied in water liquid system. The photographs of the results show that the shape of water drop that formed in the end of capillary tube is extended into a cone as well as a blue glow appears at the end of capillary tube. The size of cone decreases with increases of applied voltage and because of the change distance between the liquid electrode and the surface of liquid, the cone diameter at the end of capillary tube oscillates with period approximately 1 Sec. In addition, the PH values of both tested waters are constant when the applied voltage is less than 5 KV, while when the exterinal applied voltage is equal to or greater than 5KV, the PH value of both water types are increases rapidly where the tap water shows increases rate larger than that for distilled water.